ФОРМУВАННЯ ЕМОЦІЙНОЇ САМОРЕГУЛЯЦІЇ МАЙБУТНІХ ВИХОВАТЕЛІВ - Войтович, Оксана (Інноватика у вихованні, 2019)
Анотація. У статті аналізується проблема формування якостей емоційної сфери майбутнього вихователя, зокрема особливості її розвитку в процесі підготовки студентів до професійної діяльності. Аналізуються психолого-педагогічні дослідження проблеми. Подається визначення емоційної стійкості, емоційного вигорання та саморегуляції вихователя, аналізуються її складові, а також симптоми порушень емоційної саморегуляції та методи їх визначення (метод спостереження, бесіди, експертних оцінок, аналізу документації, тести), наводяться чинники, які їх детермінують (взаємини в колективі і з керівництвом, ставлення до об’єкта праці, негативний соціально-психологічний клімат, наявність напруженості й конфліктів у професійному середовищі). Розглядається система засобів формування емоційної стійкості та саморегуляції в процесі підготовки студентів до професійної діяльності та профілактики порушень (семінари, практичні заняття з елементами тренінгу, спрямовані на ознайомлення з особливостями професійної саморегуляції та феноменом вигоряння). Стаття містить результати експериментального дослідження з проблеми, а саме визначення рівнів емоційної стійкості та саморегуляції студентів та напрями роботи з розвитку емоційної сфери майбутніх вихователів. Корекційні техніки, представлені в статті, спрямовані на підвищення самооцінки, впевненості в собі, рівня емпатії, корекції мотивів домагань студентів.Abstract. A subject of the article is to analyze the problem of the emotional sphere qualities forming in the future preschool teacher, in particular the special aspects of its development in the preparing students for professional activity process. Psychological and pedagogical reseach of the problem are analyzed. The definition of emotional stability and self-regulation of the preschool teacher is presented, its components as well as the symptoms of the emotional self-regulation problems and methods of their determination are analyzed (surveillance, conversations, expert assessment, documentation analysis, tests), factors that determine them are presented (relationships with the group and management, attitude to the object of work, negative socio-psychological climate, the presence of tension and conflict in the professional environment). It is reviewed the system of means of forming emotional stability and self-regulation in the process of preparing students for professional activity and prevention of violations ( seminars, practical classes trainings, aimed at familiarization with the features of professional self-regulation and professional burnout phenomenon). The content of the concepts "emotional stability" and "components of emotional stability", "emotional self-regulation", "emotional burnout" are specified. The article contains the results of experimental research on the problem, namely the determination of the emotional stability levels, students' self-regulation and directions of work on the emotional sphere development of future teachers. Presented in the article correction techniques are aimed at raising self-esteem, self-confidence, empathy level, correction of motives of students' aspirations. The program envisages the work of future teachers in the areas of workload reduction, activities restructuring (competent distribution of working tasks), division of responsibilities, using of different ways of compensation of the spent efforts, tracking of results, getting gratitude from pupils' parents, self-presentation in the environment.